Next century mathematics 8 - Orines, Fernando B.; Diaz, Zenaida B.; Mojica, Maharlika P.; Manalo, Catalina B.; Suzara, Josephine L.; Mercado, Jesus P.; Esparrago, Mirla S.; Reyes, Nestor V. Jr. (Quezon City. Phoenix Publishing House, Inc., 2017)
"This textbook is enhanced with quick response (QR) codes that contain the following: Unit tests sets of questions and problems designed to make learners familiar with the types of question given in achievement tests and college entrance tests. Extra Math additional but optional topics for discussion related to the unit. For Mathiniks problems which are provided to keep the fast learners upbeat and to train him on her to become an analytical thinker, a creative problem solver, and critical observers".
Includes appendix and glossary.
English text.
Keywords: Mathematics. -- Study and teaching